In Situ Measurements of Circulation Features Influencing Cross‐Shelf Transport Around Northwest Cuba. Issue 7 (5th July 2020) - Le Hénaff, Matthieu; Kourafalou, Vassiliki H.; Androulidakis, Yannis; Smith, Ryan H.; Kang, HeeSook; Hu, Chuanmin; Lamkin, John T.
Abstract: We analyzed circulation processes sampled in the Gulf of Mexico in May 2016 by the National Oceanic and Atmospheric Administration (NOAA) Ship Nancy Foster . This data set is one of the first in situ surveys in Cuban waters available to the international community. Along northwest Cuba, these data suggested coastal upwelling and revealed, for the first time, a 50 km diameter Cuban ANticyclonic (CubAN) eddy and a 25 km diameter cyclonic eddy, which together advected upwelled waters offshore. The CubAN eddy was associated with downwelling, and the cyclonic eddy with upwelling. At the western tip of Cuba, local currents were predominantly anticyclonic, presumably due to the proximity of the retracted Loop Current, with limited export of coastal waters. Conversely, additional data from two cruises when the Loop Current was extended showed cyclonic circulation within upwelling filaments extending far offshore. These processes are important, as they can potentially entrain marine organism larvae from local reefs into the Loop Current system and to other reef ecosystems of the region. They might also affect the transport of pollutants, as hydrocarbons in case of a spill in Cuban waters. The 2016 cruise took place after the shedding of a Loop Current Ring, which involved an unusually large ( 250 km) cyclonic frontal eddy. The eddy signature was observed down to 1, 200 m depth, deeper than the Loop Current. A surface drifter revealed a low relative vorticity (0.19 f ) inside the eddy. Along its southern edge, filaments exported from the Campeche Bank were associated with high relative chlorophyll a at 3, 060 m depth. Plain Language Summary: We analyzed observations sampled in the southeastern Gulf of Mexico in May 2016 by the National Oceanic and Atmospheric Administration (NOAA) Ship Nancy Foster . Along northwest Cuba, these data showed the presence of coastal upwelling, when cold and nutrient‐rich waters are pulled to the surface along the coast under the action of the winds. A pair of ocean vortices was observed, one rotating clockwise and one counterclockwise, which together transported the upwelled waters from the coast offshore. At the western tip of Cuba, the offshore transport of coastal waters appears dependent on the state of the Loop Current, the main current of the region. This finding was based on in situ observations from two additional research cruises and satellite data. When the Loop Current is flowing close to Cuba, the transport of coastal waters is limited, whereas when it is flowing further north inside the Gulf, coastal waters can be transported far offshore. The processes revealed by the study are thus important, since they can transport marine organism larvae from coral reefs along the Cuban coast into the dynamical current system of the Gulf of Mexico and the Straits of Florida. Similarly, these processes can transport pollutants in case of an accident in Cuban waters. Key Points: A Cuban ANticyclonic (CubAN) eddy typical of the ocean circulation along northwest Cuba was observed in situ for the first time in 2016 Novel observations near northwestern Cuba show how CubANs and cyclonic eddies help advect upwelled waters offshore Along the western tip of Cuba, offshore transport of coastal waters to the Gulf of Mexico interior is dependent on the Loop Current state